2018
DOI: 10.1111/jcmm.13953
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumour microenvironment: a new vision for cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is a relatively rare malignant and lethal tumour derived from bile duct epithelium and the morbidity is now increasing worldwide. This disease is difficult to diagnose at its inchoate stage and has poor prognosis. Therefore, a clear understanding of pathogenesis and major influencing factors is the key to develop effective therapeutic methods for CCA. In previous studies, canonical correlation analysis has demonstrated that tumour microenvironment plays an intricate role in the progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 120 publications
1
25
0
Order By: Relevance
“…For instance, the incident of CCA reaches a number of approximately 7500 each year in the USA . The pathogenesis of CCA consists of primary sclerosing cholangitis, hepatolithiasis, biliary tract deformity, clonorchiasis and many others via massive signalling cascade alterations and molecule dysregulations, including non‐coding RNAs (ncRNAs) . Unfortunately, cholangiocarcinoma is still identified as a disease without effective therapeutic approaches due to the lack of effective diagnostic and prognostic biomarkers, and surgical treatments make just limited contribution to the cure of CCA .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the incident of CCA reaches a number of approximately 7500 each year in the USA . The pathogenesis of CCA consists of primary sclerosing cholangitis, hepatolithiasis, biliary tract deformity, clonorchiasis and many others via massive signalling cascade alterations and molecule dysregulations, including non‐coding RNAs (ncRNAs) . Unfortunately, cholangiocarcinoma is still identified as a disease without effective therapeutic approaches due to the lack of effective diagnostic and prognostic biomarkers, and surgical treatments make just limited contribution to the cure of CCA .…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that apoptosis was induced in KKU-213 cells after being treated with BJA-95 for 24 h. Moreover, BJA-95 increased the percentage of cells with the loss of mitochondrial transmembrane potential and the activities of caspase-3, -8 and -9, indicating that BJA-95 could induce KKU-213 cell apoptosis through the mitochondrial and caspase cascade pathways. Nuclear factor NF-κB plays an important role in countering the induction of apoptosis [34,35] by regulating the transcription of apoptotic-related genes, such as Bcl-2 [36][37][38], thus modulating the survival and growth of various cancers, including CCA. In this study, we found that the expression level of NF-κB was reduced by BJA-95 treatment, which was consistent with the decreased expression levels of anti-apoptotic proteins and the increased expression levels of pro-apoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In the crosstalk between CAFs and cancer cells, exosomes play an important role [91,99]. Exosomes are membrane-wrapped extracellular vesicles containing microRNAs, DNA fragments, proteins, and other soluble factors.…”
Section: D Models: Cell Lines and Primary Cell Culturesmentioning
confidence: 99%